VD_FINDINFO HC / 2011 / 541 vom 12. September 2011 - VD Tribunal cantonal (2011)
PROTECTION DE L'UNION CONJUGALE, LOGEMENT DE LA FAMILLE, ATTRIBUTIONSENS GÉNÉRAL | 176 al. 1 ch. 2 CC, 179 al. 1 CC, 308 al. 1 CPC, 317b al. 1 CPC